Časovno odvisna simulacija, vizualizacija in meritve kavitacije z metodo PIV-LIF na različnih osamljenih profilih - Dular, Matevž (Strojniški vestnik, 2005)
This paper concerns a numerical and experimental study of cavitating flow around different single hydrofoils. The program package Fluent was used to calculate the unsteady flow, and the homogeneous flow principle was used to describe two-phase flow. The cavitation model based on a simplified Rayleigh-Plesset equation for bubble dynamics, was used to describe the appearance and collapse of a cavitation cloud. A 3D transient simulation of cavitating flow under different conditions for two hydrofoils was made. Images of the vapour structures under different cavitation conditions for the two hydrofoils were acquired. A PIV-LIF method was used to obtain the velocity field inside and outside the vapour cavity. Measurements of the cavitation cloud shedding frequencies were made. Numerically predicted distributions of the water vapour and the velocity field were compared with experimental results. The experimentally determined and numerically predicted mean cavity structure lengths along the hydrofoil were compared. Also, a comparison between the numerically predicted and the experimental cavitation cloud shedding frequencies was made. In all cases a good correlation between the experimental results and the numerical simulations was found. The simulation was also able to correctly predict the formation of typical "horseshoe" cavitation structures.
Keywords: kavitacija; dinamika tekočin; vizualizacija; metoda PIV-LIF